Metformin and Gegen Qinlian Decoction boost islet α-cell proliferation of the STZ induced diabetic rats - Li Xu; Shreyas Jois; Hongliang Cui (BMC, 2022)
Abstract Background The traditional Chinese medicine Gegen Qinlian Decoction (GQD), as well as metformin, had been reported with anti-diabetic effects in clinical practice. Objective To verify whether these two medicines effectively ameliorate hyperglycemia caused by deficiency of islet β-cell mass which occurs in both type 1 and type 2 diabetes. Methods SD rats were injected with a single dose of STZ (55 mg/kg) to induce β-cell destruction. The rats were then divided into control, diabetes, GQD and metformin group. GQD and metformin groups were administered with GQD extract or metformin for 6 weeks. The islet α-cell or β-cell mass changes were tested by immunohistochemical and immunofluorescent staining. The potential targets and mechanisms of GQD and metformin on cell proliferation were tested using in silico network pharmacology. Real-time PCR was performed to test the expression of islet cells related genes and targets related genes. Results Both GQD and metformin did not significantly reduce the FBG level caused by β-cell mass reduction, but alleviated liver and pancreas histopathology. Both GQD and metformin did not change the insulin positive cell mass but increased α-cell proliferation of the diabetic rats. Gene expression analysis showed that GQD and metformin significantly increased the targets gene cyclin-dependent kinase 4 (Cdk4) and insulin receptor substrate (Irs1) level. Conclusion This research indicates that GQD and metformin significantly increased the α-cell proliferation of β-cell deficiency induced diabetic rats by restoring Cdk4 and Irs1 gene expression.